2020
DOI: 10.7759/cureus.9766
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Otitis Media in Children Referred to Abuzar Hospital in Ahvaz: A Case-Control Study

Abstract: Hardani et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Clinical evidence from the literature seems to be in favor of an association between allergic rhinitis/atopic status and OME, whereas results about a hypothetical correlation with AOM and RAOM are contradictory and inconclusive because one of the major critical points is that some authors fail to distinguish among the different phenotypes of middle ear inflammation in children (articles included in the qualitative analyses are reported in Table 2). Salah et al did not find evidence linking allergy to AOM/RAOM, 10 whereas authors 11‐13 demonstrated that AR in children may increase the risk of otitis, even if they failed in distinguishing among different phenotypes of OM. Accordingly, authors 34,35 demonstrated that atopic children may have a significantly increased risk of recurrent or persistent OM needing repeated tympanostomy tube insertions without distinguishing between AOM and OME.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical evidence from the literature seems to be in favor of an association between allergic rhinitis/atopic status and OME, whereas results about a hypothetical correlation with AOM and RAOM are contradictory and inconclusive because one of the major critical points is that some authors fail to distinguish among the different phenotypes of middle ear inflammation in children (articles included in the qualitative analyses are reported in Table 2). Salah et al did not find evidence linking allergy to AOM/RAOM, 10 whereas authors 11‐13 demonstrated that AR in children may increase the risk of otitis, even if they failed in distinguishing among different phenotypes of OM. Accordingly, authors 34,35 demonstrated that atopic children may have a significantly increased risk of recurrent or persistent OM needing repeated tympanostomy tube insertions without distinguishing between AOM and OME.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have documented that AR patients have a higher risk of ET dysfunction, particularly during childhood, than non‐allergic ones 12,43 . Therefore, AR seems to be a common risk factor in children with OME and there is significant hearing loss compared to non‐AR children with OME; in addition, the hearing level improved significantly with medical therapy 11 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations